Development and validation of REAGERA-P, a new questionnaire to evaluate health care provider preparedness to identify and manage elder abuse - Johanna Simmons; Marika Wenemark; Mikael Ludvigsson (BMC, 2021)
Abstract Background Elder abuse is prevalent and associated with morbidity but often goes unnoticed in health care. Research on the health care response to victims calls for valid measurements. This article describes the development and validation of a questionnaire to evaluate health care provider preparedness to care for older adults subjected to abuse, the REAGERA-P (Responding to Elder Abuse in GERiAtric Care - Provider questionnaire). Method REAGERA-P was developed in phase I. The questionnaire includes a case vignette, self-efficacy scales for identifying and managing elder abuse cases and cause for concern as well as organizational barriers when talking with older patients about abuse. Content validity was ensured by a review committee, and cognitive interviews were conducted to ensure face validity and to examine cognitive processes to ensure comprehension. REAGERA-P was then administered to health care providers (n = 154, response rate 99 %) to test for construct validity. Factor analysis was performed, and internal consistency was tested for the self-efficacy scales. Convergent validity was tested by investigating associations between relevant variables. Some items were revised in phase II, and new cognitive interviews were performed. Parts of the questionnaire were tested for responsiveness by administering it to medical interns (n = 31, response rate 80 %) before and after an educational intervention. Results REAGERA-P showed good content and face validity. The factor analysis revealed two factors: one for asking questions about abuse (Cronbach's α = 0.75) and one for managing the response to the questions (Cronbach's α = 0.87). Results suggest good convergent validity for the self-efficacy scales and for questions about cause for concern and organizational barriers. The responsiveness of the self-efficacy scales was good: the mean on the scale for asking questions (range 0-30) was 15.0 before the intervention and 21.5 afterwards, the mean on the scale for managing the response (range 0-50) was 22.4 before the intervention and 32.5 afterwards. Conclusion REAGERA-P is a new questionnaire that can be used to evaluate health care provider preparedness to identify and manage cases of elder abuse, including educational interventions conducted among staff to improve health care responses to victims of elder abuse. This initial testing of the questionnaire indicates that the REAGERA-P has good validity.